Discovery of N-quinazolinone-4-hydroxy-2-quinolone-3-carboxamides as DNA gyrase B-targeted antibacterial agents. (31st December 2022) - Xue, Wenjie; Wang, Yaling; Lian, Xu; Li, Xueyao; Pang, Jing; Kirchmair, Johannes; Wu, Kebin; Han, Zunsheng; You, Xuefu; Zhang, Hongmin; Xia, Jie; Wu, Song
Abstract: Emerging drug resistance is generating an urgent need for novel and effective antibiotics. A promising target that has not yet been addressed by approved antibiotics is the bacterial DNA gyrase subunit B (GyrB), and GyrB inhibitors could be effective against drug-resistant bacteria, such as methicillin-resistant S. aureus (MRSA). Here, we used the 4-hydroxy-2-quinolone fragment to search the Specs database of purchasable compounds for potential inhibitors of GyrB and identified AG-690/11765367, or f1, as a novel and potent inhibitor of the target protein (IC50 : 1.21 µM). Structural modification was used to further identify two more potent GyrB inhibitors: f4 (IC50 : 0.31 µM) and f14 (IC50 : 0.28 µM). Additional experiments indicated that compound f1 is more potent than the others in terms of antibacterial activity against MRSA (MICs: 4–8 µg/mL), non-toxic to HUVEC and HepG2 (CC50 : approximately 50 µM), and metabolically stable (t1/2 : > 372.8 min for plasma; 24.5 min for liver microsomes). In summary, this study showed that the discovered N-quinazolinone-4-hydroxy-2-quinolone-3-carboxamides are novel GyrB-targeted antibacterial agents; compound f1 is promising for further development.